2005
DOI: 10.1007/s10517-006-0059-6
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory degeneration of joint tissue in adjuvant arthritis after intraarticular treatment with the mixture of silver drug and nicotinic acid

Abstract: Combination intraarticular administration of Poviargol (0.5 mg/kg) and nicotinic acid (1.0 mg/kg) reduced symptoms of local and general inflammation in rats with adjuvant arthritis. We revealed a decrease in morphological signs of inflammatory degeneration of joint tissue and reduction of metabolic disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…In addition, HCA2 has been found to be expressed by various immune cells including macrophages, neutrophils, and epidermal Langerhans cells 19 20 41 42 , and the expression in macrophages is increased by treatment with IFN-γ in combination with TNF-α, lipopolysaccharide, and CpG oligodeoxynucleotides 20 . Recent studies revealed that niacin possesses anti-inflammatory activities in various tissues/cell types via HCA2 18 27 28 29 30 43 44 . Interestingly, activation of HCA2 by niacin significantly inhibited chemokine-induced migration of macrophages 18 34 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, HCA2 has been found to be expressed by various immune cells including macrophages, neutrophils, and epidermal Langerhans cells 19 20 41 42 , and the expression in macrophages is increased by treatment with IFN-γ in combination with TNF-α, lipopolysaccharide, and CpG oligodeoxynucleotides 20 . Recent studies revealed that niacin possesses anti-inflammatory activities in various tissues/cell types via HCA2 18 27 28 29 30 43 44 . Interestingly, activation of HCA2 by niacin significantly inhibited chemokine-induced migration of macrophages 18 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Niacin has been shown to suppress TNF-α-induced release of proinflammatory chemokines thus reducing chemokine MCP-1 (CCL2)-induced recruitment of macrophages into the atherosclerotic lesions 18 24 25 26 . Interestingly, recent in vitro and in vivo studies have revealed anti-inflammatory roles of niacin in acute ischemic stroke, arthritis, chronic renal failure and sepsis 27 28 29 30 31 32 , suggesting that niacin not only inhibits vascular inflammation, but also has therapeutic potential in other systemic inflammatory and metabolic diseases.…”
mentioning
confidence: 99%
“…A niacinmediated beneficial cardiovascular effect has been shown to be transferable with GPR109A-competent bone marrow cells (21). In addition, accumulating evidence has demonstrated that activation of GPR109A was able to induce anti-inflammatory effects not only on atherosclerosis but also on acute ischemic stroke, arthritis, chronic renal failure, and sepsis through inhibition of immune cell chemotaxis and proinflammatory cytokine production (20)(21)(22)(23)(24)(25)(26)(27)(28)(29). Therefore, more studies are needed to thoroughly evaluate the GPR109A-mediated pleiotropic effects on atherogenesis and other metabolic diseases.…”
mentioning
confidence: 99%